THE INFLUENCE OF TALENT MANAGEMENT, WORK ENVIRONMENT, AND COMPETENCE ON EMPLOYEE PERFORMANCE AT THE DEPARTMENT OF COOPERATIVES, MICRO ENTERPRISES, INDUSTRY, AND TRADE OF BINTAN REGENCY - Bobby Ansyari Hasibuan; Sumardin; Suyono; Sabri (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to determine the influence of talent management, work environment, and competence on employee performance at the Cooperatives, Micro Enterprises, Industry, and Trade Office of Bintan Regency. The population in this study amounted to 80 respondents, using a saturated sampling technique so that the entire population became the sample, namely 80 respondents. The sampling technique was carried out with a saturated sample. Data collection was carried out by distributing questionnaires to respondents. The collected data were processed using SPSS software. The results of the study indicate that partially, Talent Management has a significant effect on employee performance with a significance value of <0.001 (<0.05), Work Environment has a significant effect on employee performance with a significance value of 0.002 (<0.05), and Competence has a significant effect on employee performance with a significance value of <0.001 (<0.05). Simultaneously, talent management, work environment, and competence have a significant effect on employee performance with a significance value of <0.001 (<0.05). The Adjusted R Square value is 0.999 or 99.9%, which means that talent management, work environment, and competence are able to explain 99.9% of employee performance variations, while the remaining 0.1% is influenced by other variables not discussed in this study.